Comparative study on design of braced excavation systems - Toh, Yan Ting (2019)
The Finite Element Method is commonly used to analyse braced excavations to ensure the stability of the braced excavation and assess the ground movements to minimise damage to nearby buildings. In this study, PLAXIS 2D was used to analyse three excavation case studies namely Ministry of Environment (MOE) Building, Lavender MRT Station and Farrer Park Kandang Kerbau (FPKK). For each case study, three soil stress-strain models (Mohr-Coulomb, Hardening Soil and Hardening Soil with small-strain stiffness) were studied. Back analysis was carried out to determine the E50/cu that gave a good agreement to the measured wall deflections for each of the soil stress-strain models. The settlement profiles were also determined for comparison. Using this E50/cu value, partial factors analysis based on Eurocode 7 Design Approach 1 (DA1) was carried out using PLAXIS 2D to obtain the design strut forces and wall bending moments. Design Approach 1 consists of Combination 1, Combination 2 Scheme 1 and Combination 2 Scheme 2. The design values were retrieved for comparison. Additionally, the partial factor for cu was varied to assess its sensitivity on excavation performance. Lastly, in view of the deflection guidelines set by the Building and Construction Authority (BCA), the lateral deflection for each of the case studies were verified and the excavation design was modified to meet the deflection requirements. From this study, the following findings are drawn: The Hardening Soil and the Hardening Soil with small-strain stiffness models generate conservative settlement profiles compared to the Mohr-Coulomb model; Combination 1 provides a conservative estimation of the wall bending moments; Upper strut forces are more conservative using DA1 Combination 1 while bottom strut forces are more conservative using DA1 Combination 2 Scheme 1; Scheme 2 gives a large bending moment than Scheme 1; The Mohr-Coulomb model, generally, gives a smaller maximum wall bending moment than the Hardening Soil model; findings from sheet pile excavation deviate from those from diaphragm wall excavations; and lastly, consideration of factored E50/cu ratio produces similar strut forces and bending moments compared to unfactored E50/cu values.